Analisis Pengaruh Jumlah Penduduk Dan Harga Terhadap Permintaan Air Minum PDAM Tirtanadi Cabang Medan Denai - Yenni Samri Juliati (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
This study aims to determine the effect of population and price on demand for drinking water. This type of research is quantitative using primary data, the analytical method used is multiple regression using Statistical Package for Social Science (SPSS) computer software. The results of this study indicate that the variable population influences the demand for drinking water PDAM Tirtanadi Medan Denai Branch. The price variable does not influence the demand for drinking water PDAM Tirtanadi Medan Denai Branch. Variable number of population and price jointly influence the demand for drinking water PDAM Tirtanadi Medan Denai Branch.